The influence of physical exercise on college students’ life satisfaction: The chain mediating role of self-control and psychological distress - Zhou, Guang-Yu; Yang, Bin; Li, Hao; Feng, Quan-Sheng; Chen, Wan-Yi (Frontiers in Psychology, 2023)
Objective To explore the relationship between physical exercise and life satisfaction among college students and test the dual mediating role of self-control and psychological distress between them. Methods A sample of 526 Chinese college students completed questionnaires regarding physical exercise, life satisfaction, self-control and psychological distress, of which 38.4% were boys. Results Path analyzes indicated that physical exercise was positively correlated with life satisfaction, and this link could be mediated by self-control and psychological distress. Conclusion The present study identifies the potential underlying mechanism by which physical exercise is associated with the life satisfaction of college students, which has important implications for theory and prevention.